2016
DOI: 10.1111/codi.13333
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of a transanal endoscopic microsurgery programme: initial experience with surgical performance

Abstract: Operative efficiency appears to improve as surgeons completed 16 TEM cases. We have identified important factors that result in longer operating time. The study has important implications with regard to surgical training and operative planning for new TEM programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The introduction of the single use TAMIS platforms has facilitated the implementation of minimally invasive techniques for transanal excision in many surgeons’ practices . However, the procedure can be technically challenging to learn, and even skilled laparoscopic surgeons require experience with many procedures to attain technical competence . The option of leaving a rectal defect unsutured is appealing early in the learning curve when operative times may be long.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of the single use TAMIS platforms has facilitated the implementation of minimally invasive techniques for transanal excision in many surgeons’ practices . However, the procedure can be technically challenging to learn, and even skilled laparoscopic surgeons require experience with many procedures to attain technical competence . The option of leaving a rectal defect unsutured is appealing early in the learning curve when operative times may be long.…”
Section: Discussionmentioning
confidence: 99%
“…The learning curve is still an obstacle to integrating this procedure into surgeons’ repertoire . Endoluminal suturing is particularly difficult and inability to suture through transanal platforms has been a barrier to technique adoption.…”
Section: Introductionmentioning
confidence: 99%
“…The TEM rectoscope is an expensive technology for a hospital not already using it for colorectal operations. Additionally, there is a surgical learning curve is estimated between 14 and 24 cases (11,12). …”
Section: Discussionmentioning
confidence: 99%
“…Helewa et al report a leveling of the learning curve measured by the time of operation of 16 cases, with a second plateau at 35 cases. 15 Barendse et al showed a learning curve effect on conversion to laparoscopy, procedure length, and complication rate that all decreased with increasing experience. 16 Learning curve data on this technique is difficult to interpret as many surgeons will expand indications to include more proximal or larger lesions which in turn increases operating times.…”
Section: Transanal Endoscopic Surgery Educationmentioning
confidence: 99%